Sixth cervical vertebra with bilateral double foramen transversarium and non-bifid spine: a rare case - Mishra, Gyan Prakash; Kumari, Sangeeta; Bhatnagar, Shobha; Singh, Brijendra (International Journal of Research in Medical Sciences, 2017)
Anatomical knowledge of variations is of utmost clinical importance to all of us as they may be one of the reasons as etiological as well as of surgical importance. Vertebral region also presents many variations. Foramen transversarium are typical feature of cervical vertebrae and give way to neurovascular bundle, like vertebral artery, vertebral veins and sympathetic plexus around them throughout. Foramen transversarium and spine or spinous process of cervical vertebrae are important to all of medical specialists as well as for surgeons specially the surgeons dealing with head & neck surgeries. Knowledge of anatomical/surgical variations is very important for neurosurgeons and radiologists for reporting and planning for surgeries as this type of variation if ignored may be a cause for fatal or undesirable outcome of the surgical procedure or may lead to a different planning/approach at the time or during the surgical procedure. In the present case we observed very uncommon finding of bilateral double foramen transversarium as well as a nonbifid spinous process in sixth cervical vertebra which is extremely rare. Right and left both main foramen transversarium were bilateral symmetrical and rounded in shape. Right accessory foramen transversarium was complete while left was incomplete. Finding of present study is important in neurosurgery for posterior approaches of the cervical vertebrae and also useful for radiological studies to avoid erroneous counting of cervical spines in clinical observations as surface landmark.